Gutenberg's Europe the book and the invention of western modernity - Barbier, Frederic (Cambridge, UK Polity Press, 2017)
"Major transformations in society are always accompanied by parallel transformations in systems of social communication--what we call the media. In this book, historian Frederic Barbier provides an important new economic, political and social analysis of the first great 'media revolution' in the west: Gutenberg's invention of the printing press in the mid-fifteenth century. In great detail and with a wealth of historical evidence, Barbier charts the developments in manuscript culture in the twelfth and thirteenth centuries, and shows how the steadily increasing need for written documents initiated the processes of change which culminated with Gutenberg. The fifteenth century is presented as the 'age of start-ups', an era of flourishing investment and research into technologies that were new at the time, including the printing press."' -- Provided by publisher
"Tracing the developments through the sixteenth century, Barbier analyses the principal features of this first media revolution: the growth of technology, the organization of the modern literary sector, the development of surveillance and censorship and the invention of the process of 'mediatization'. He offers a rich variety examples from cities all over Europe, as well as looking at the evolution of print media in China and Korea"--Provided by publisher.
Introduction: the media and change -- Chapter 1 The preconditions for a new economy of the media -- Chapter 2 The economy of the book -- Chapter 3 The birth market -- Chapter 4 The development and logics of innovation -- Chapter 5 Gutenberg and the invention of printing -- Chapter 6 Innovation -- Chapter 7 Printing conquers the world -- Chapter 8 The nature of text -- Chapter 9 The media explosion
First published in french as L'Europe de Gutenberg, Le livre et l'invention de la modernite occidentale (XIII-XVI siecle), Editions Belin, 2006.
Includes index.
Keywords: Gutenberg, Johann -- 1397?-1468.; Printing -- History -- Origin and antecedents; Books -- History; Europe -- Civilization